Réponses

2014-03-09T19:45:17+01:00
Salut :)

f = 2 ( 4x - 5) + (5x+7) - 3 (8 +5x)
f = 2 x 4x + 2 x (-5) + 5x + 7 - 3 x 8 - 3 x 5x
f = 8x - 10 + 5x + 7 - 24 - 15x
f = -2x - 27

g = -5 (-1 + 3x²) - x(5+x)-2x(3-2x)
g = -5 x (-1) - 5 x 3x² - (x) x 5 - (x) x (x) - 2x x 3 - 2x x (-2x)
g = 5 - 15x² - 5x - x² - 6x + 4x²
g = -12x² - 11x + 5

h = (2x-3) (3x-8)
h = 2x x 3x + 2x x (-8) - 3 x 3x - 3 x (-8)
h = 6x² - 16x - 9x + 24
h = 6x² - 25x + 24

i = (x-1) (5x-2) - [(3x-6) (-1 + x)]

i = (x) x 5x + (x) x (-2) - 1 x 5x - 1 x (-2) - (3x x (-1) + 3x x (x) - 6 x (-1) - 6 x (x))
i = 5x² - 2x - 5x + 2 - (-3x + 3x² + 6 - 6x)
i = 5x² - 7x + 2 + 3x - 3x² - 6 + 6x
i = 2x² + 2x - 4

J'espère t'avoir aidé(e)! :)